Effect of Product Quality and Service Quality on Customer Loyalty with Customer Satisfaction as an Intervenning Variables (Case Study on the Tirta Jasa Lampung Selatan Regional Company (PDAM)) - Lukman Nuzul Hakim (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2021)
This study aims to determine the effect of Product Quality and Service Quality on Customer Satisfaction and Loyalty at the Tirta Jasa Regional Drinking Water Company (PDAM), Lampung Selatanar. The sample used is 220 (10 times the number of research indicators there are 22), the data analysis used is path analysis SEM (Structural Equation Modeling) model processed with the Amos version 22 program.The results of this study found that: Directly, product quality has a positive and significant effect on customer satisfaction and also on customer loyalty. Directly, service quality has a positive and significant effect on customer satisfaction and also on customer loyalty. Directly and indirectly, product quality has a positive and significant effect on customer loyalty. Directly and indirectly service quality has a positive and significant effect on customer loyalty. Customer satisfaction has a positive and significant direct effect on customer loyalty.